The Role of Education and Cognitive Growth in Shaping Characters - Kakharova , Mohigul (INTERNATIONAL MULTIDISCIPLINARY SCIENCE CONFERENCE, 2026)
The article is about the dynamic personal development of Jack London’s protagonist Martin Eden which is compared to Bloom’s Taxonomy: remembering, understading, applying and so on. Moreover, it also discusses the novel of “Mirage” by A.Qahhor. The events experienced in A. Qahhor’s life served as the basis for his novel “Mirage”. The author’s humanistic and taciturn qualities are reflected in the character of Saidiy in “Mirage”.